2019
DOI: 10.1038/s41477-019-0526-5
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the sites of non-photochemical quenching in vascular plants

Abstract: In nature, plants experience large fluctuations in light intensity and they need to balance the absorption and utilization of this energy accordingly. Non-photochemical quenching (NPQ) is a rapidly-switchable mechanism which protects plants from photodamage caused by high light exposure by dissipating the energy absorbed in excess as heat. It is triggered by the ΔpH across the thylakoid membrane and requires the presence of the protein PsbS and the xanthophyll zeaxanthin. However, the site and mechanism of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
113
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 61 publications
7
113
1
Order By: Relevance
“…2). This agrees with the consensus that NPQ is predominantly located in the major antennae of chlorophytes and vascular plants (Goral et al, 2012;Nicol et al, 2019), and that D. armatus has a constitutively small antennae protein network.…”
Section: Diurnal Changes In Psii Functional Antenna Sizesupporting
confidence: 90%
See 1 more Smart Citation
“…2). This agrees with the consensus that NPQ is predominantly located in the major antennae of chlorophytes and vascular plants (Goral et al, 2012;Nicol et al, 2019), and that D. armatus has a constitutively small antennae protein network.…”
Section: Diurnal Changes In Psii Functional Antenna Sizesupporting
confidence: 90%
“…This process becomes important for avoiding damage to the photosynthetic system when absorbed light energy cannot be fully utilized by the light-harvesting reactions. NPQ is triggered by a DpH gradient across the thylakoid membrane that leads to conformational changes in the light-harvesting antennae associated with PSII (Goral et al, 2012;Nicol et al, 2019).…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that PsbS-dependent NPQ occurs mainly in the LHCII whereas another quenching site operates within the PSII core complex (Nicol et al, 2019). For plants containing the Lx cycle and green algae exhibiting the shortened Vx/Ax cycle it was demonstrated that L or Ax can play a similar role in NPQ induction and enhancement as it is normally observed for Zx (Goss et al, 1998;Garcia-Plazaola et al, 2003;Leonelli et al, 2017).…”
Section: Function Of Xanthophyll Cyclesmentioning
confidence: 96%
“…Apart from the xanthophyll zeaxanthin, PsbS is known as another component of NPQ [51]. PsbS-dependent quenching site has been recently deciphered to be in Light-harvesting complex II (LHCII), and in the PSII core, most likely in the core antenna complexes CP43 and/or CP47 [52]. In the study of Giacomelli and coworkers, PsbS protein was up-regulated more than twofold upon transition to high light, however, it remained unchanged in the vtc2, which is in line with the observation that vtc2 mutants have reduced levels of non-photochemical quenching [47].…”
Section: Role Of Ascorbate In Light Acclimationmentioning
confidence: 99%